Lipidated α/Sulfono-α-AA heterogeneous peptides as antimicrobial agents for MRSA. Issue 1 (1st January 2020) - Singh, Sylvia; Wang, Minghui; Gao, Ruixuan; Teng, Peng; Odom, Timothy; Zhang, En; Xu, Hai; Cai, Jianfeng
Graphical abstract: Highlights: Design and synthesis of 13 lipidated α/Sulfono-α-AA heterogeneous peptides as mimics for Host defense peptides. Lipidated α/Sulfono-α-AA heterogeneous peptides can efficiently eradicate Gram-positive bacteria. Synthesized lipidated α/Sulfono-α-AA heterogeneous peptides capable of selecting bacterial cells over human red blood cells. Abstract: Though antibiotics have been used for decades to treat bacterial infections, there is a great need for new treatment methods. Bacteria are becoming resistant to conventional antibiotics, as is the case with Methicillin resistant Staphylococcus aureus (MRSA). Herein we report the design of a series of lipidated α/Sulfono-α-AA heterogeneous peptides as mimics for Host Defense Peptides (HDPs). Utilizing fluorescence microscopy and depolarization techniques, our compounds demonstrate the ability to kill Gram-positive bacteria through cell membrane disruption. This mechanism of action makes it difficult for bacteria to develop resistance. Further time kill studies and hemolytic assays have also proven these compounds to be efficient in their ability to eradicate bacteria cells while remaining non-toxic to human red blood cells. This new class of peptidomimetics shows promise for the future antibiotic treatment of MRSA.